Development of an electronic data collection tool for clinical studies - Dr Regina Catherine Benavente Hansson; Dr Fernando J Mota de Almeida; Associate Professor Specialist in Endodontics Annika E Björkner (Elsevier, 2023)
Aim or Purpose: To quality assure and simplify the data collecting procedure for scientific multicenter clinical studies by using a novel digitalization process. Materials and Methods: A website with digital protocols allowing attachment of radiographic images (Sunet Survey) was created in collaboration with the Communication department and the Vice-chancellor office at Malmö University, Sweden to create a user-friendly navigation.The website consists of two linked sites, with access for the patients and the dental team. The patient site includes general information about the study and consent of participation. The dental team site includes a chronological sequence that guides the team from the patient's initial visit through the entire treatment including postoperative controls. The participating dentist records data one single time about standard medicaments and dental equipment to be used during treatments.Randomization information is printed on cards for the team and the patient showing elected treatment, login details and a QR-code to gain easy access. Results: Test pilots of the analogue paper and the digital procedure were evaluated. The remote real-time data collection allows the researchers to monitor the data collection from the clinics without disclosing the patient's identity. Retrieving of digital data collection enables the research team to verify that data is collected from all participating clinics. The real-time collection offers a safety feature. Conclusions: The website increases research quality assurance, saves time, and provides an easy overview of the process. Using electronic tools for data collection makes it simple for the clinical team to collect data and easier for the research group to monitor that data collection takes place.